Evaluation of degree of upper aerodigestive tract obstruction in patients with snoring and obstructive sleep apnea syndrome - Rajanna, Lohith B.; Muniraju, Bharath; Kumar, Santosh; Reddy, N. Madhav; Malleshappa, Vikram (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Objectives of the study were to evaluate the degree of obstruction of upper aerodigestive tract in patients with snoring and obstructive sleep apnea syndrome (OSAS) by nasopharyngolaryngoscopy assisted Muller’s maneuver; to evaluate the degree of obstruction of upper aerodigestive tract in patients with snoring and OSAS with imaging technique magnetic resonance imaging (MRI); and to find the association between fibroptic nasopharyngolaryngoscopy assisted Muller’s maneuver (NMM) and sleep MRI. Methods: Study design was open prospective observational study. 30 patients diagnosed with snoring and OSA were included in the study at department of ear, nose and throat (ENT), Command Hospital, Air Force, Bangalore. They underwent detailed clinical evaluation and polysomnography followed by assessment of levels and degree of obstruction of upper aerodigestive tract by flexible fiber optic laryngoscopy (FOL) assisted Mullers maneuver and functional (f) sleep MRI. Results: 20 patients (66.7%) were diagnosed as obstructive sleep apnea syndrome, 10 patients (33.3%) were snorers by Polysomnography. 27 (90%) patients show moderate to severe collapse at level of the base of tongue, 25 (83.3) patients show moderate to severe collapse at the level of soft palate by flexible FOL assisted Mullers maneuver. 22 (73.4%) patients show a collapse the level of the soft palate, 20 (66.6%) patients show a collapse at the level of the base of tongue by f sleep MRI. In this study, on applying Chi square test there was significant association between soft palate Flexible nasopharyngoscopy with muller’s method and soft palate MRI with Chi square value 35.690, p value <0.001. There was significant association between base of tongue flexible nasopharyngoscopy with Muller’s method and base of tongue sleep MRI with Chi-square value 14.511, and p value <0.005. Conclusions: Polysomnography is gold standard test to diagnose OSA. Flexible nasopharyngoscopy with Muller’s method and sleep MRI shows the most common site of upper airway collapse is at the level of the soft palate and the base of tongue.